The impact of relying on artificial intelligence in managing cyber crises on the reputation of the organization, from the perspective of corporate communications officials in Riyadh (The International Journal for Scientific Research, 2026)
This study aimed to investigate the impact of relying on Artificial Intelligence (AI) in cyber crisis management on corporate reputation, from the perspective of specialists within private sector companies in the Kingdom of Saudi Arabia. The study focused on three main axes: the current status of employing AI technologies across various crisis stages, the impact of such usage on enhancing reputation dimensions, and the identification of challenges hindering this application. To achieve the research objectives, the researcher adopted the descriptive survey method due to its suitability for the study's nature, utilizing a questionnaire as the primary data collection tool. The study population comprised corporate communication officials in Saudi private sector companies in Riyadh. The study was conducted on a convenience sample of (80) specialists distributed across various sectors. The results indicated a very high level of reliance on AI in crisis management, with a mean of (4.28). Specifically, operations involving the analysis of attack sources and the isolation of affected systems topped the list of applied practices. The findings also demonstrated a very high positive impact of these technologies on enhancing corporate reputation (4.23), effectively contributing to increased customer trust, data protection, and strengthened competitive positioning. Conversely, the study revealed substantial obstacles limiting effectiveness (mean: 4.32), foremost among them being high financial costs and a shortage of qualified human personnel. Consequently, the study recommended the development of automated linkage systems to ensure rapid media response, the adoption of human review mechanisms to ensure credibility, and the formulation of governance policies to regulate AI usage.
Keywords: Artificial Intelligence; Cyber Crises; Corporate Reputation; Crisis Management; Corporate Communication; Cybersecurity